Redesain Alat Pemeras Santan Kelapa Dengan Menggunakan Metode Antropometri - Zulfahmi; Meri Andriani; Yusnawati (CV. ALIM'SPUBLISHING, 2024)
East Aceh is one of the areas producing coconut plants, which have great benefits in everyday human life from the roots and stems to the shoots. Coconut milk is one of the ingredients used to make typical Acehnese food. The problem that exists when squeezing coconut milk is still manually using your hands. Strong force is needed to squeeze the coconut milk to get thick coconut milk, so housewives complain of pain in the upper arms and lower arms, especially the fingers. The research aims to determine the dimensions of the design and ergonomic measurements of the tool. The research method is anthropometry and statistical tests. From the results and discussion, it was obtained that five dimensions were determined, a data adequacy test was carried out with the results of all the data being declared valid, the uniformity test stated that all the data was uniform and all the data was declared to have a normal distribution. The percentiles used are different, where the 95th percentile (P95) is used for the dimensions of the width of the palm (metacarpal) (LTM), and the width of the palm (up to the thumb) (LTB), while the 5th percentile (P5) is used for the dimension of hand length (PT). , forearm length (PLB), upper arm length (PLA). In conclusion, the ergonomic measurements obtained were 15.88 cm for tool handle diameter, 31.03 cm for tool height, 23.60 cm for tool lever length, 10.33 cm for tool handle length, and 10.67cm for tube diameter. Kata kunci: Perancangan, Antropometri, Ergonomis.